Mediator Complex Subunit 19 Promotes the Development of Hepatocellular Carcinoma by Regulating the AKT/mTOR Signaling Pathway - Zhang, Yuting; Qin, Peifang; Xu, Xingfeng; Li, Mao; Huang, Haitao; Yan, Jianguo; Zhou, Yali (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors, the pathogenesis of which remains unclear. Mediator complex subunit 19 (MED19), a subunit of the Mediator complex, is a multi-protein co-activator necessary for DNA transcription factors to induce RNA polymerase II transcription. In the current study, we aimed to study the role of MED19 in HCC and elucidate its mechanism. Methods: MED19 expression in HCC tissues was determined. The relationship between MED19 and the clinical prognosis was explored. The influence of MED19 on HCC cell viability, migration, invasion, and apoptosis was studied. The expression of AKT/mTOR pathway genes and proteins was detected by qRT-PCR and western blot. The correlation between MED19 and immune infiltration was investigated. Results: MED19 was upregulated in HCC tissues compared with tumor-adjacent tissues, and was associated with a poor prognosis. Furthermore, high MED19 expression was correlated with race, gender, etc. Knockdown of MED19 inhibited cell proliferation, migration, invasion, and promoted apoptosis. Knockdown of MED19 decreased p-AKT and p-mTOR protein expression. Additionally, the downstream effectors of the AKT/mTOR pathway, p70S6K1 and 4EBP1, were affected by MED19. Notably, MED19 expression was positively correlated with the infiltration levels of B cells, CD4+ T cells, CD8+ T cells, macrophages, etc. Conclusion: MED19 is significantly upregulated in HCC tissues and cells. MED19 may promote the progression of HCC in vitro and may be related to immune infiltration. Together, our data show that MED19 could be considered as a new possible biomarker as well as a novel therapeutic target for HCC.